Achieving high-performance epoxy nanocomposites with trifunctional poly(oxypropylene)amines functionalized graphene oxide. (June 2019) - Sun, Tong; Zou, Huawei; Zhou, Ya; Li, Rui; Liang, Mei; Chen, Yang
In this article, two types of functional graphene oxide (GO) with amine-rich surface were synthesized through chemically grafting two different molecular chain length trifunctional poly(oxypropylene)amines T5000 and T403, which were named as T5000-GO and T403-GO, respectively. The functionalized GO was then added to epoxy (EP) resin. Fourier transform infrared spectra analysis confirmed successful chemical functionalization on GO. Both T403-GO and T5000-GO were tightly embedded in the EP, because the amine-rich surface of functionalized-GO could form covalent bonds with the EP matrix, thereby contributing to the enhancement of mechanical properties. Particularly, T5000-GO, which has longer grafting molecule chains, achieved better compatibility and dispersibility in the EP matrix, resulting in a better reinforcing efficiency in mechanical properties. For example, the T5000-GO/EP composites showed an incremental enhancement in tensile strength with increasing filler concentrations, whereas their T403-GO/EP counterparts failed to follow the same trend. Meanwhile, the T5000-GO/EP composites with only 0.1-wt% T5000-GO achieved a prominent increase in flexural strength (approximately 50%) and flexural modulus (approximately 26.8%), which were higher than those of T403-GO-filled counterparts. This work indicated that the compatibility and interphase between GO and EP could be designed by manipulating the length of grafting molecule chains, thereby providing a better understanding of the relationship between the structure and mechanical properties of the graphene/EP nanocomposites.